A Tribute to Harold McIver Leich on His Retirement and on Being Accorded the 2019 ASEEES CLIR Distinguished Service Award. (3rd April 2021) - Giullian, Jon C.; Harris, Grant G.
ABSTRACT: Harold M. Leich's outstanding service as a Slavic librarian from 1969 to 2019 earned him the Distinguished Service Award of the Committee on Libraries and Information Resources, delivered during the 2019 annual convention of the Association for Slavic, East European, and Eurasian Studies (ASEEES). He began as a cataloger at the University of Illinois at Urbana-Champaign, where six years later he was promoted to Librarian for Slavic and East European Acquisitions. From 1987 until retirement he served at the Library of Congress as Russian Area Specialist. For his last 20 years there he also served as the specialist for Modern Greek. He assisted Dr. James H. Billington, the Librarian of Congress and noted scholar of Russia, with many projects. Over his career, Leich produced more than 50 publications, mostly concerning Russian materials, but also on Modern Greek collections as well as on book matters relating to other countries. He participated on many ASEEES committees, and he also served on committees for the American Library Association, the Modern Greek Studies Association, and other societies.